2010
DOI: 10.3390/rs2051320
|View full text |Cite
|
Sign up to set email alerts
|

Global Evaluation of Radiosonde Water Vapor Systematic Biases using GPS Radio Occultation from COSMIC and ECMWF Analysis

Abstract: Abstract:In this study, we compare specific humidity profiles derived from Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) radio occultation (RO) from August to November 2006 with those from different types of radiosonde and from ECMWF global analysis. Comparisons show that COSMIC specific humidity data agree well with ECMWF analysis over different regions of the world for both day and night times. On the contrary, evaluation against COSMIC specific humidity shows a distinct dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 17 publications
3
95
0
1
Order By: Relevance
“…Kursinski et al (1997), Rocken et al (1997), Kursinski and Hajj (2001), and Colard and Healey (2003) described the retrieval process of humidity profiles from GPSRO observations. Steiner et al (1999), Gorbunov and Kornblueh (2001), Divakarla et al (2006), Ho et al (2007), Chou et al (2009), Ho et al (2010, Sun et al (2010), Gorbunov et al (2011), Kishore et al (2011), Wang et al (2013, and Vergados et al (2014) validated the GPSRO-based humidity retrievals against reanalyses, radiosondes, and satellite observations, while recently Kursinski and Gebhardt (2014) reported an innovative technique to further reduce and eliminate retrieval biases in the middle-troposphere humidity products.…”
Section: Introductionmentioning
confidence: 99%
“…Kursinski et al (1997), Rocken et al (1997), Kursinski and Hajj (2001), and Colard and Healey (2003) described the retrieval process of humidity profiles from GPSRO observations. Steiner et al (1999), Gorbunov and Kornblueh (2001), Divakarla et al (2006), Ho et al (2007), Chou et al (2009), Ho et al (2010, Sun et al (2010), Gorbunov et al (2011), Kishore et al (2011), Wang et al (2013, and Vergados et al (2014) validated the GPSRO-based humidity retrievals against reanalyses, radiosondes, and satellite observations, while recently Kursinski and Gebhardt (2014) reported an innovative technique to further reduce and eliminate retrieval biases in the middle-troposphere humidity products.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al (2007) combined AIRS and RO data retrieving SH profiles in the lower troposphere with root-mean-square error (RMSE) between 0.40 g kg −1 (at 700 hPa) and 0.05 g kg −1 (at 400 hPa). Ho et al (2010) collocated RO and ECMWF profiles near radiosonde locations and estimated that the standard deviation of the differences between the two data sets is < 0.50 g kg −1 above 3.0 km altitude. Kishore et al (2011) estimated that the differences between the ERA-Interim and COSMIC are −0.15±0.22 g kg −1 at 3.0 km and −0.07±0.06 g kg −1 at 7.0 km in the deep tropics (±20 • ).…”
Section: Atmospheric Infrared Soundermentioning
confidence: 99%
“…The RS at the four stations are generally launched twice daily during the hour before . The VIZ/Sippican B2 humidity sensor has a nighttime wet bias (Wang and Zhang, 2008;Ho et al, 2010), and performs poorly in dry conditions (H. Vömel, personal communication, 2017). Ho et al (2010) found no obvious bias for the Meisei sensor.…”
Section: Radiosonde Airs and Gfsmentioning
confidence: 99%
“…The VIZ/Sippican B2 humidity sensor has a nighttime wet bias (Wang and Zhang, 2008;Ho et al, 2010), and performs poorly in dry conditions (H. Vömel, personal communication, 2017). Ho et al (2010) found no obvious bias for the Meisei sensor. The Vaisala RS92 sensor is known for its dry bias (Vömel et al, 2007) of ∼9 % at surface, and up to 50 % at 15 km altitude, and several correction schemes have been developed to address this 5 (Miloshevich et al, 2006;Vömel et al, 2007).…”
Section: Radiosonde Airs and Gfsmentioning
confidence: 99%